2015
DOI: 10.1186/s13104-015-1384-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro anti-inflammatory and antibacterial potential of Crescentia cujete leaves and stem bark

Abstract: BackgroundThe various parts of Cresecentia cujete have some important biological activities. In folklore medicine leaves are used to treat hematomas, tumors and hypertension. Fruit decoction is used to treat diarrhea, stomachaches, cold, bronchitis, cough, asthma, and urethritis. The present study was designed to explore the anti-inflammatory and antibacterial potential of C. cujete leaves and stem bark. Anti-inflammatory activity was evaluated by in vitro human red blood cell (HRBC) membrane stabilization met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 23 publications
2
34
0
7
Order By: Relevance
“…Berenuk (Crescentia cujete, Linn.) merupakan salah satu tanaman yang bisa digunakan sebagai herbal (Parvin et al, 2015). Tumbuhan ini tersebar diberbagai daerah di Indonesia dan umum untuk dijumpai.…”
Section: Pendahuluanunclassified
“…Berenuk (Crescentia cujete, Linn.) merupakan salah satu tanaman yang bisa digunakan sebagai herbal (Parvin et al, 2015). Tumbuhan ini tersebar diberbagai daerah di Indonesia dan umum untuk dijumpai.…”
Section: Pendahuluanunclassified
“…La cratylia ha sido poco estudiada en términos de compuestos fitoquímicos, aunque se reporta la presencia de fenoles y taninos, en muy bajas proporciones (AGROSAVIA, 2018), siendo considerada como una especie baja en taninos (Stürm et al, 2007). En lo que respecta al totumo, ha sido estudiado por sus propiedades antioxidantes, antiinflamatorias y antibacteriales, lo que se le atribuye a la presencia de compuestos fenólicos (Lizcano et al, 2010;Das et al, 2014;Parvin et al, 2015).…”
Section: T Diversifoliaunclassified
“…[10] Moreover, extensive research has indicated that the leaves and stems of Crescentia cujeta have antiinflammatory and antibacterial properties-thus, the plant extract has therapeutic potential against bacterial infection and disease processes of the body. [11] One remedy that is commonly used on both people and animals is engine oil for the treatment on sarcoptic and demodectic mange. This treatment has shown to be effective in clogging the pores of the epidermis while suffocating the parasitic mites within the hair follicles.…”
Section: Introductionmentioning
confidence: 99%